Au Nanoparticles Effect on Inverted ZnO Nanorods/Organic Hybrid Solar Cell Performance - Pham Hoai Phuong; Kang Jea Lee; Huynh Tran My Hoa; Hoang Hung Nguyen; Quang Trung Tran; Nguyen Thi Hai Yen; Tran Viet Cuong (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
The sun provides a plentiful and inexpensive source of carbon-neutral energy that has yet to be fully utilized. This is a major driving force behind the development of organic photovoltaic (OPV) materials and devices, which are expected to offer benefits such as low cost, flexibility, and widespread availability. For the photovoltaic performance enhancement of the inverted ZnO-nanorods (NR)/organic hybrid solar cells with poly(3-exylthiophene):(6,6)-phenyl-C61-butyric-acid-methylester (P3HT:PCBM) and poly (3,4-ethylenedioxythiophene):poly (styrenesulfonate) (PEDOT:PSS) active layers, gold nanoparticles (Au-NPs) were introduced into the interface between indium-thin-oxide cathode layer and ZnO cathode buffer layer, and the efficiency improvement was observed. It's worth noting that adding Au NPs had both a positive and negative impact on device performance. Au NPs were shown to be advantageous to localized surface plasmon resonance (LSPs) in the coupling of dispersed light from ZnO NRs in order to extend the light's path length in the absorbing medium. Although the light absorption in the active layer could be enhanced, Au NPs might also act as recombination centers within the active layer. To avoid this adverse effect, Au NPs are covered by the ZnO seeded layer to prevent Au NPs from direct contact with the active layer. The dominant surface plasmonic effect of Au NPs increased the photoelectric conversion efficiency from 2.4% to 3.8%.